Fahrenheit and the premature burial of interactive movies - Lessard, Jonathan (Eludamos: Journal for Computer Game Culture, 2009)
Interactive movies have the bad reputation of combining the worst of cinema and video games. The success of the game Fahrenheit (released in North America as Indigo Prophecy) in 2006 might lead us to reevaluate this failure. This articles argues that this game can be considered an updated form of interactive movie and discusses some of this genre’s characteristics that are still relevant and attractive today: artistically motivated mise-en-scène and rich storytelling.